Musculoskeletal pain, kinesiophobia, and quality of life in obese patients - Ercan, Sabriye; Küçük, Furkan; Örsçelik, Aydan; Çetin, Cem (The European Research Journal, 2023)
Objectives: This study aims to examine musculoskeletal pain, kinesiophobia, and quality of life in individuals with normal body mass index and in individuals with obesity, and to determine the relationship between the variables. Methods: In the study; individuals aged between 20-65 years, with a body mass index of 30 kg/m2 and above (Group obesity) with obesity, and individuals with a range of 18.5-24.9 kg/m2 (Group normal) were included. General Practice Physical Activity Questionnaire, Orebro Musculoskeletal Screening Questionnaire, Short Form-12 Health Survey, and Kinesiophopia Causes Scale were applied to the participants for primary care. Results: When the descriptive characteristics of the individuals in the sample which were divided into two groups as the Group normal (n = 82; 22.6 ± 1.7 kg/m2) and Group obesity (n = 92; 33.0 ± 2.8 kg/m2 were analyzed; while a difference was determined in terms of sex, education level and presence of chronic disease (p ˂ 0.05), no difference was found in terms of age, marital status and regular drug use for the treatment of chronic disease (p ˃ 0.05). Although the activity level rates of Group obesity were lower according to the physical activity questionnaire classification for primary care, no statistically significant difference was found between the groups (p = 0.090). More musculoskeletal pain was found in the individuals of the obesity group (p = 0.003), the physical sub-dimension score of the general quality of life questionnaire was negatively affected (p = 0.014), and a difference in favor of phobia was determined in all domains of the kinesiophobia causes scale (p < 0.001). There was a weak positive correlation between body mass index and musculoskeletal pain, while a moderate positive correlation with kinesiophobia. Conclusions: Although physical activity level is similar to individuals with normal body mass index, musculoskeletal pain and kinesiophobia are higher in individuals with obesity, and their quality of life is negatively affected.